DFT/TD-DFT Study of D–π–A dyes explore the NLO properties - Ali, Aqeel; Toama, Nooraldeen (University of Thi-Qar Journal of Science, 2023)
The molecular structures and optical properties of six different N.dimethylphenylendiamino dyes were analyzed using a combination of DFT functionals (B3LYP and Cam-B3LYP/6-311+G(p,d)). The six dyes are D1-D6. The various parameters of the solvated phase, such as the polarizabilities, hyperpolarizabilities, peak absorption wavelengths, and HOMO-LUMO energy gaps, were calculated and analyzed. The results of the study are in agreement with the results of the NLO activity order thiophene linker > pyrrole bridge. Compared to the dipyrrole versions, the designed dithiophene-linker dyes exhibit longer absorption wavelengths and smaller HOMO-LUMO gaps. The predicted first hyperpolarisability of dyes D1-D3 are higher than that of D4-D5. This is mainly due to its enhanced electron-withdraw ability and the long p-conjugating action of the thiophene moiety. Highly elevated total hyperpolarisability of the designed dyes, suggests its potential application in organic NLO devices, which is expected to be useful.